(untitled) (Journal of Maternal and Child Health, 2024)
Background: Breast cancer is the most common cancer and the leading cause of cancer death in women worldwide. The implementation of the program in reducing the incidence of breast cancer is focused on prevention based on evidence of risk factors. This study aims to estimate factors that influence the incidence of breast cancer in women of productive age. Subjects and Method: This study used systematic review and meta-analysis using PICO. Population: Women of productive age. Interventions: menstruation at ≥13years, parity (multipara) and using hormonal contraceptives. Comparison: menstruation at <13years, parity (nullipara) and not using hormonal contraceptives. Result: breast cancer. The articles used in this study came from 2 databases, namely Google Scholar and BMC. The keywords of the article were "menarche" AND "parity" AND "risk factor" AND "breast cancer". The articles included in this study were full paper articles, used case control study designs, publication year ranged from 2014-2023, and measure of association was in Adjusted Odds Ratio. Articles were analyzed using the Review Manager 5.4 application. Results: Thirteen case-control studies indicated that women who menstruated at ≥13 years old lowered the likelihood of breast cancer by 0.69 times (aOR=0.69; CI 95%= 0.57 to 0.84; p= 0.001). Eleven case-control studies indicated that multiparous parity lowered the likelihood of breast cancer by 0.49 times (aOR=0.49; CI 95%= 0.34 to 0.72; p= 0.001). Eleven case-control studies indicated that using contraception increased the likelihood of breast cancer by 1.47 times (aOR=1.47; CI 95%= 1.12 to 1.93; p= 0.006). Conclusion: Menstruation age <13 years old, parity (nullipara) and use of hormonal contraceptives are predictors in breast cancer cases in women of productive age.